Fixing member for electrophotography, fixing device and electrophotographic image forming apparatus
The electrophotographic fixing member, featuring an elastic layer with silicone rubber, thermally conductive filler, and negatively charged charge control agent, addresses the issue of elastic layer breakdown due to long-term high-temperature use, ensuring durability and high-quality image formation.
Patent Information
- Application Number
- JP2021125683
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-08
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-07-30
AI Technical Summary
The elastic layer in heat fixing devices for electrophotographic image forming devices, containing thermally conductive fillers, tends to break due to long-term use at high temperatures, especially when the hardness of the elastic layer is reduced.
An electrophotographic fixing member is developed with a substrate, an elastic layer containing silicone rubber and thermally conductive filler, and a surface layer. The elastic layer includes a negatively charged charge control agent to prevent aggregation of thermally conductive fillers, enhancing the breaking energy and durability of the elastic layer.
The proposed solution provides an electrophotographic fixing member with excellent durability, preventing the elastic layer from breaking even after long-term use at high temperatures, and enabling stable formation of high-quality electrophotographic images.
Smart Images

Figure 0007654502000008 
Figure 0007654502000009 
Figure 0007654502000010
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fixing member used in an electrophotographic image forming apparatus, a fixing device, and an electrophotographic image forming apparatus. [Background technology]
[0002] In general, in a heat fixing device used in an electrophotographic image forming apparatus such as a copying machine or a printer, a pair of heated rollers, a film and a roller, a belt and a roller, or a belt and a belt are in pressure contact with each other. These rotating bodies are called fixing members. Then, a recording material holding an image formed by unfixed toner is introduced into a pressure contact portion (fixing nip) formed between these rotating bodies. Then, the unfixed toner is heated together with the recording material, and the toner is pressed against the recording material while softening and melting, so that the image is fixed on the recording material. The rotating body that the toner held on the recording material comes into direct contact with functions as a heating member, and may have a roller shape, a film shape, or a belt shape. In addition, the rotating body that forms the fixing nip together with the heating member functions as a pressing member, and may have a roller shape, a film shape, or a belt shape, like the heating member. Among these fixing members, the fixing member (heating member) that comes into direct contact with the toner held on the recording material and heats the toner is required to be able to supply heat to the recording material and the toner in the fixing nip to soften and melt the toner. Therefore, it has been proposed to incorporate a thermally conductive filler such as magnesium oxide or metal silicon into the elastic layer of the fixing member in order to increase its thermal conductivity (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 3-221982 [Patent Document 2] JP 2007-171946 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, according to the study by the present inventors, a fixing member having an elastic layer containing a thermally conductive filler to improve thermal conductivity may have a tendency to break when used at high temperatures for a long period of time, and this tendency is particularly noticeable when the hardness of the elastic layer is reduced. Therefore, in order to extend the service life of a fixing member having an elastic layer with enhanced thermal conductivity by containing a thermally conductive filler, the inventors have come to recognize that it is necessary to develop a new technology to prevent breakage of the elastic layer caused by the inclusion of the thermally conductive filler. One aspect of the present disclosure is directed to providing an electrophotographic fixing member having excellent durability, in which the elastic layer does not break even after long-term use despite having an elastic layer containing a thermally conductive filler. Another aspect of the present disclosure is directed to providing a fixing device and an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Means for solving the problem]
[0005] According to one aspect of the present disclosure, there is provided an electrophotographic fixing member having a substrate, an elastic layer on the substrate, and a surface layer in this order, the elastic layer containing silicone rubber and a thermally conductive filler dispersed in the silicone rubber, the thermally conductive filler being metal oxide particles or metal particles having at least a part of their surface constituted by metal oxide, and the elastic layer further containing a charge control agent negatively charged with respect to the thermally conductive filler. According to another aspect of the present disclosure, there is provided a fixing device including the fixing member. According to another aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including the fixing member. [Brief description of the drawings]
[0006] [Figure 1] 1A and 1B are explanatory diagrams of a presumed mechanism of the effect exhibited by the fixing member according to one embodiment of the present disclosure. [Diagram 2] 2A is an overhead view of a corona charger for forming an elastic layer of a fixing member according to an embodiment of the present disclosure, and FIG. 2B is a cross-sectional view of a corona charger for forming an elastic layer of a fixing member according to an embodiment of the present disclosure. [Diagram 3] 3A and 3B are schematic cross-sectional views of fixing members according to the present disclosure in belt and roller form, respectively. [Figure 4] FIG. 2 is a schematic diagram illustrating an example of a step of laminating a fluororesin surface layer. [Diagram 5] 1 is a schematic cross-sectional view of an example of a fixing device in which a fixing member according to the present disclosure is disposed. [Figure 6] FIG. 2 is a schematic perspective view of a jig for evaluating the pressure resistance durability of an elastic layer according to the present disclosure. [Figure 7] FIG. 2 is an explanatory diagram of the arrangement of thermally conductive fillers formed in a mixture layer whose surface is charged. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present inventors speculate as follows as to the reason why the elastic layer breaks when the fixing roll according to Patent Document 1 or the fixing belt according to Patent Document 2 is used at high temperatures for a long period of time. 1A, in the elastic layer 4, the thermally conductive filler 4b is dispersed in the silicone rubber 4a serving as a binder, and it is believed that there are aggregated portions 401 of the filler 4b. Then, in the process of repeatedly compressing the elastic layer 4, fracture occurs in the elastic layer 4 starting from the aggregated portions 401 of the filler 4b. Here, if the degree of cross-linking of the silicone rubber 4a is reduced to reduce the hardness of the elastic layer 4, the strength of the silicone rubber itself around the aggregated portions 401 is reduced, and it is believed that fracture of the elastic layer 4 is more likely to occur. Based on these considerations, the inventors conducted further research and discovered that an elastic layer containing, in addition to silicone rubber and a thermally conductive filler, a charge control agent (hereinafter simply referred to as "charge control agent") that is negatively charged relative to the thermally conductive filler can have excellent durability. The reason why such an elastic layer can have excellent durability is presumed to be as follows. That is, the elastic layer is formed by curing an addition-curing liquid silicone rubber mixture in which a thermally conductive filler is dispersed. In this addition-curing liquid silicone rubber mixture, the thermally conductive filler is positively charged by shear with the liquid silicone rubber, but the amount of charge of the thermally conductive filler is non-uniform. Therefore, it is considered that the thermally conductive filler that is almost not charged or the thermally conductive filler with a small amount of charge generates the aggregation part 401. On the other hand, the elastic layer according to one embodiment of the present disclosure is formed by curing an addition-curing liquid silicone rubber mixture in which a thermally conductive filler and a charge control agent are dispersed. In the preparation process of the addition-curing liquid silicone rubber mixture, as shown in FIG. 1B, the thermally conductive filler 4b and the charge control agent 4c are close to each other or contact each other, so that the thermally conductive filler 4b is positively charged. It is believed that the charge control agent 4c is used to actively charge the thermally conductive filler 4b positively, thereby making it difficult for differences in the amount of charge of the thermally conductive filler 4b to occur. As a result, in the addition-curing liquid silicone rubber mixture, aggregation between the thermally conductive filler 4b is suppressed, and the formation of aggregation parts 401 (see FIG. 1A) of the thermally conductive filler 4b is inhibited. As a result, it is believed that the breaking energy of the elastic layer 4 increases. The breaking energy is the area of a stress-strain curve obtained by subjecting the elastic layer to a tensile breaking test, and the larger the breaking energy, the more difficult it is for the elastic layer to break.
[0008] The present disclosure will now be described in detail with reference to the drawings. (1) Fixing member The configuration of the electrophotographic fixing member according to the present disclosure will be described with reference to the drawings. 3A and 3B are schematic cross-sectional views showing two embodiments of the fixing member according to the present disclosure. FIG. 3A shows a fixing member having an endless belt shape (hereinafter, also referred to as a "fixing belt"), and FIG. 3B shows a fixing member having a roller shape (hereinafter, also referred to as a "fixing roller"). The fixing members according to FIGS. 3A and 3B have, in this order, a base body 3, an elastic layer 4 containing silicone rubber covering the outer peripheral surface of the base body 3, and a surface layer 6 covering the outer peripheral surface of the elastic layer 4. Note that the adhesive layer 5 between the elastic layer 4 and the surface layer 6 is optional. For example, when the surface layer 6 is formed by melting fluororesin particles attached to the outer peripheral surface of the elastic layer 4, the adhesive layer 5 may not be included.
[0009] (2) Substrate When the fixing member is a fixing belt as shown in FIG. 3A, the substrate can be made of a metal such as an electroformed nickel sleeve or a stainless steel sleeve, or a heat-resistant resin such as polyimide. A layer for imparting a function of improving adhesion to the elastic layer can be provided on the outer surface (the surface on the elastic layer side) of the substrate. That is, the elastic layer only needs to be provided on the outer peripheral surface of the substrate, and other layers can be provided between the elastic layer and the substrate. In addition, a layer for imparting functions such as wear resistance and lubricity can be further provided on the inner surface (the surface opposite to the outer surface) of the substrate. When the fixing member is a fixing roller as shown in Fig. 3B, the base only needs to have a strength that can withstand the heat and pressure in the fixing device, and can be, for example, a core made of a metal such as aluminum or iron or an alloy. In Fig. 3B, a solid core is used as the base, but a hollow core may also be used for the base, and a heat source such as a halogen lamp may be provided inside.
[0010] (3) Elastic layer The fixing member according to the present disclosure can be used as either a heating member or a pressure member in a fixing device. When used as a heating member, the elastic layer functions as a layer for making the outer surface of the heating member follow the unevenness of the paper during fixing. When used as a pressure member, the elastic layer functions as a layer for ensuring a sufficient width of the fixing nip formed between the heating member and the pressure member. In order to realize these functions in an environment where the non-paper passing area is as high as 240°C, the elastic layer contains silicone rubber having excellent heat resistance as a binder. That is, the elastic layer contains silicone rubber and a heat conductive filler dispersed in the silicone rubber. The elastic layer can be formed by curing an addition-curing liquid silicone rubber mixture containing, for example, a thermally conductive filler and an addition-curing liquid silicone rubber. That is, the elastic layer can be a cured product of the addition-curing liquid silicone rubber mixture. The elastic layer can also contain a cured product of the addition-curing liquid silicone rubber, a thermally conductive filler present in the cured product, and a charge control agent that is negatively charged with respect to the thermally conductive filler. The Asker C hardness (hereinafter simply referred to as "hardness") of the elastic layer based on the Japanese Industrial Standards (JIS) K7312:1996 is preferably 50° or less. When the hardness is 50° or less, the elastic layer does not break or plastically deform even when repeatedly compressed at high temperatures, and has excellent flexibility. The hardness of the elastic layer can be adjusted, for example, by changing the type and amount of component (a), component (b), and component (c) in the addition-curing liquid silicone rubber described below. The silicone rubber, the thermally conductive filler and the charge control agent, which are the components of the elastic layer, will be described in detail below. (3-1) Silicone rubber The addition-curable liquid silicone rubber contains at least the following components (a), (b) and (c), and optionally contains component (d). (a) Organopolysiloxane having an unsaturated aliphatic group in the molecule (b) Organopolysiloxane having active hydrogen bonded to silicon atoms (c) Hydrosilylation catalyst (d) Hardening retarder
[0011] Component (a): Organopolysiloxane having an unsaturated aliphatic group in the molecule Examples of organopolysiloxanes having an unsaturated aliphatic group in the molecule include organopolysiloxanes containing an unsaturated aliphatic group such as a vinyl group that is bonded to at least two silicon atoms in one molecule.Specific examples include organopolysiloxanes according to the following (i) and (ii).
[0012] (i) R1R1S i The intermediate unit represented by O and R1R2S i and one or both intermediate units selected from the group consisting of intermediate units represented by R1R1R2S i O 1 / 2 and a linear organopolysiloxane having a molecular end represented by the following structural formula 1.
[0013] [ka]
[0014] (ii) R1R1S i One or both of intermediate units selected from the group consisting of intermediate units represented by O and intermediate units represented by R1R2SiO, and R1R1R1SiO 1 / 2 and a linear organopolysiloxane having a molecular end represented by the following structural formula 2.
[0015] [ka]
[0016] In Structural Formula 1 and Structural Formula 2, R1 each independently represents an unsubstituted hydrocarbon group that does not contain an unsaturated aliphatic group, R2 each independently represents an unsaturated aliphatic group, and m and n each independently represent an integer of 0 or greater.
[0017] In addition, examples of the unsubstituted hydrocarbon group not containing an unsaturated aliphatic group represented by R1 in structural formula 1 and structural formula 2 include alkyl groups such as methyl, ethyl, and propyl groups, and aryl groups such as phenyl groups. Among these, R1 is preferably a methyl group. In addition, examples of the unsaturated aliphatic group represented by R2 in structural formula 1 and 2 include alkenyl groups such as vinyl, allyl, and 3-butenyl groups. Among these, R2 is preferably a vinyl group.
[0018] In structural formula 1, linear organopolysiloxanes where n=0 have unsaturated aliphatic groups only at both ends, while linear organopolysiloxanes where n=1 or more have unsaturated aliphatic groups at both ends and in the side chain. The linear organopolysiloxane of structural formula 2 has unsaturated aliphatic groups only in the side chain. The (A) component may be used alone or in combination of two or more types.
[0019] When the component (A) is used in the elastic layer of the fixing member, the viscosity is set to 100 mm from the viewpoint of moldability. 2 / s or more, 50000mm 2 It is preferable that the ratio is 1 / s or less. (b) an organopolysiloxane having active hydrogen atoms bonded to silicon atoms; The crosslinking agent for component (a), which is an organopolysiloxane having active hydrogen bonded to a silicon atom, is a crosslinking agent that forms a crosslinked structure through a hydrosilylation reaction with the unsaturated aliphatic groups in component (a) due to the catalytic action of component (c), which will be described later. As the component (b), any organopolysiloxane having a Si-H bond can be used, and examples thereof include the organopolysiloxanes (iii) to (iv) below. Note that the component (b) may be used alone or in combination of two or more types.
[0020] (iii) From the viewpoint of forming a crosslinked structure by reaction with an organopolysiloxane having an unsaturated aliphatic group, an organopolysiloxane having an average of 3 or more hydrogen atoms bonded to silicon atoms per molecule. (iv) Organopolysiloxanes in which the organic group bonded to the silicon atom is an unsubstituted hydrocarbon group that does not contain an unsaturated aliphatic group as described above, wherein the unsubstituted hydrocarbon group is preferably a methyl group. In the organopolysiloxane of component (b), the siloxane skeleton (-Si-O-Si-) may be linear, branched, or cyclic. The Si-H bond may be present in any siloxane unit in the molecule. Specifically, the linear organopolysiloxanes shown in the following structural formulas 3 and 4 can be used as component (b).
[0021] [ka]
[0022] [ka]
[0023] In structural formula 3 and structural formula 4, R1 each independently represents an unsubstituted hydrocarbon group not containing an unsaturated aliphatic group, p represents an integer of 0 or more, and q represents an integer of 1 or more. Examples of the unsubstituted hydrocarbon group not containing an unsaturated aliphatic group include the same as those represented by R1 in structural formulas 1 and 2, and a methyl group is preferable.
[0024] The blend amount of the component (b) is preferably 0.1 to 20 parts by mass, and more preferably 0.3 to 10 parts by mass, per 100 parts by mass of the component (a).
[0025] (c) Hydrosilylation catalyst As the hydrosilylation (addition curing) catalyst, for example, a platinum compound can be used. Specific examples include platinum carbonylcyclovinylmethylsiloxane complex, 1,3-divinyltetramethyldisiloxane platinum complex, etc. The blending amount of component (c) is preferably 0.0001 to 0.1 parts by mass, more preferably 0.001 to 0.05 parts by mass, per 100 parts by mass of component (a).
[0026] (d) Hardening retarder A curing retarder can be added to adjust the curing reaction rate of hydrosilylation (addition curing). Specific examples of the curing retarder include 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane, 2-methyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol. The amount of component (d) added is preferably 0.01 to 2 parts by mass, more preferably 0.05 to 1 part by mass, per 100 parts by mass of component (a).
[0027] (3-2) Thermally conductive filler The thermally conductive filler may be at least one type selected from the group consisting of metal oxide particles and metal particles at least a portion of the surface of which is composed of a metal oxide. Such thermally conductive fillers include, for example, magnesium oxide, silicon metal, alumina and zinc oxide. The thermal conductivity of magnesium oxide is 45~60 W / m·K, that of silicon metal is 150 W / m·K, that of zinc oxide is 50 W / m·K, and that of alumina is 40 W / m·K. The thermal conductivity of silicone rubber without fillers is about 0.2 W / m K, so by incorporating these thermally conductive fillers into silicone rubber, the thermal conductivity of the elastic layer can be increased. The content of the thermally conductive filler in the elastic layer is preferably 10% or more and 55% or less in terms of volume percentage of the total filler. If the total filler amount is 10% or more in volume percentage, the thermal conductivity of the elastic layer made of silicone rubber can be sufficiently increased, and if it is 55% or less, the elastic layer made of silicone rubber can fully exhibit its elastic function as rubber.
[0028] (3-3) Charge control agent The above-mentioned metal oxide particles as the thermally conductive filler and metal particles at least part of whose surface is composed of a metal oxide can be positively charged. The order of ease of being positively charged is considered to be magnesium oxide, metal silicon at least part of whose surface is oxidized, zinc oxide, and alumina. Examples of negatively chargeable charge control agents capable of imparting a positive charge to these thermally conductive fillers include salicylic acid metal complexes and azo metal complexes. Among them, azo metal complexes are more preferable from the viewpoint of heat resistance. Examples of azo metal complexes include iron-based and chromium-based complexes. Regarding heat resistance, since the temperature of the fixing member at the non-paper passing portion may reach about 240°C, heat resistance that is stable at a temperature range higher than that is desirable, and it is particularly desirable that the thermal decomposition starting temperature of the charge control agent is 300°C or higher. Specific examples of charge control agents having such heat resistance include compounds represented by the following structural formulas (i) and (ii).
[0029] [ka]
[0030] The compound according to structural formula (i) is commercially available, for example, under the trade name "S-215S" (manufactured by Orient Chemical Industries, Ltd.), and the compound according to structural formula (ii) is commercially available, for example, under the trade name "S-34" (manufactured by Orient Chemical Industries, Ltd.) Other negatively charged charge control agents that can be mentioned as candidates are those that are mainly used in toners. The amount of the charge control agent is preferably 1 part by mass or more and 5 parts by mass or less per 100 parts by mass of silicone rubber. When the amount is 1 part by mass or more, the effect of increasing the breaking energy is obtained. Also, when the amount is 5 parts by mass or less, sufficient hardness is obtained in the non-paper passing portion of the silicone rubber elastic layer. The dispersion state of the charge control agent is not particularly limited, but it is more preferable if the charge control agent is dispersed in the silicone rubber in the form of particles having a diameter of 1 μm or less, since this may facilitate the effect of increasing the breaking energy.
[0031] (3-4) Method for manufacturing elastic layer As a non-limiting example of a method for producing the elastic layer according to one embodiment of the present disclosure, the layer of the addition curing type liquid silicone rubber mixture (hereinafter also referred to as the "mixture layer") can be formed through a process of curing. Here, it is preferable to charge the outer surface of the mixture layer prior to curing the mixture layer. This allows the thermally conductive filler in the mixture layer to be aligned in the thickness direction, and the thermal conductivity of the elastic layer in the thickness direction can be further increased. As an embodiment for arranging the thermally conductive filler in the mixture layer in the thickness direction, a method using a corona charger will be described. Corona charging methods include a scorotron method having a grid electrode between the corona wire and the charged body, and a corotron method not having a grid electrode. From the viewpoint of controllability of the surface potential of the charged body, the scorotron method is preferred.
[0032] 2A and 2B, the corona charger 2 includes blocks 201 and 202, shields 203 and 204, and a grid 206. A discharge wire 205 is stretched between the blocks 201 and 202. A high voltage power supply (not shown) applies a high voltage to the discharge wire 205, and the ion flow obtained by discharge to the shields 203 and 204 is controlled by applying a high voltage to the grid 206, thereby charging the surface of the mixture layer 401. At this time, since the base 3 or the core 1 holding the base 3 is grounded (not shown), it is possible to generate a desired electric field in the mixture layer 401 by controlling the surface potential of the surface of the mixture layer 401.
[0033] 2A, the corona chargers 2 are disposed closely facing each other along the width direction of the mixture layer 401. Then, a voltage is applied to the grid 206 of the corona charger 2, and in a discharged state, the core 1 is rotated in the direction of the arrow A2 to rotate the base 3 having the mixture layer 401 on its outer circumferential surface at 100 rpm for 20 seconds, for example, to charge the outer surface of the mixture layer 401. The distance between the outer surface of the mixture layer 401 and the grid 206 can be 1 mm to 10 mm. In this way, the surface of the mixture layer 401 is charged, and an electric field is generated in the mixture layer 401. As a result, as shown in FIG. 7, among the thermally conductive fillers in the mixture layer 401, for example, small particle size fillers 701 having a circle equivalent diameter of less than 5 μm can be aligned in the thickness direction of the mixture layer 401. On the other hand, among the thermally conductive fillers, for example, large particle size fillers 703 having a circle equivalent diameter of 5 μm or more hardly change position in the mixture layer 401, and are polarized to generate a local electric field between the large particle size fillers. This electric field can align the small particle size fillers located between the large particle size fillers. In FIG. 7, the arrow 705 indicates the thickness direction of the mixture layer. Here, the reason why the small particle size fillers can be highly aligned while suppressing the alignment of the large particle size fillers by charging the surface of the mixture layer 401 is considered to be as follows. That is, even if the surface of the mixture layer 401 is charged, it is considered difficult to apply a force to the large particle size filler 703 that is sufficient to move the position of the large particle size filler 703 in the mixture layer by dielectrophoresis. However, dielectric polarization occurs in the large particle size filler 703, and a local electric field is formed between the large particle size fillers 703. As a result, the local electric field acts on the small particle size filler 701 present between the large particle size fillers 703, and it is considered that the small particle size filler 701 is highly aligned between the large particle size fillers 703. As a result, it is considered that a heat conduction path is formed in the thickness direction of the mixture layer, in which the large particle size fillers 703 are connected by the small particle size fillers.
[0034] From the viewpoint of generating an effective electrostatic interaction with the thermally conductive filler, the voltage applied to the grid 206 is preferably in the range of 0.3 kV to 3 kV, particularly 0.6 kV to 2 kV, in absolute value. Note that, although an example in which the surface of the mixture layer 401 is positively charged is shown in Figures 2A and 2B, if the sign of the applied voltage is made the same as the sign of the voltage applied to the wire, the effect obtained is the same whether the voltage is negative or positive, although the direction of the electric field will be reversed.
[0035] The ease of alignment of the small particle size filler in the mixture layer 401 is considered to depend on, for example, the dielectric constants of the binder raw material and the thermally conductive filler. For example, when the difference between the dielectric constant of the binder raw material and the dielectric constant of the thermally conductive filler is large, the small particle size filler can be aligned with a relatively small applied voltage. Therefore, it is preferable to appropriately adjust the voltage applied to the grid depending on the combination of the material used for the binder raw material and the type of thermally conductive filler.
[0036] The range of potential control in the longitudinal direction of the surface of the mixture layer 401 is preferably equal to or larger than the paper passing area of the fixing member. For example, the configuration shown in FIG. 2A can be used, and while a voltage is applied to the grid 206, the entire mixture layer 401 can be charged by rotating the substrate having the mixture layer 401 around the central axis of the substrate as the rotation axis. The rotation speed of the fixing belt is preferably 10 rpm to 500 rpm, and the treatment time is preferably 5 seconds or more from the viewpoint of stably forming an array of the small particle size filler. From the above, the formation of the array of the small particle size filler can be controlled by controlling the surface potential and the time for applying the electric field.
[0037] The discharge wire 205 may be made of any of a variety of materials, including stainless steel, nickel, molybdenum, and tungsten, and is preferably made of tungsten, which is one of the most stable metals. The shape of the discharge wire 205 stretched inside the shields 203 and 204 is not particularly limited, and may be, for example, a sawtooth shape or a circular cross-sectional shape (circular cross-sectional shape) when the discharge wire is cut vertically. The diameter of the discharge wire 205 (at the cut surface when cut vertically to the wire) is preferably 40 μm or more and 100 μm or less. If the diameter of the discharge wire 205 is 40 μm or more, it is possible to easily prevent the discharge wire from being cut or broken due to the collision of ions caused by discharge. If the diameter of the discharge wire 205 is 100 μm or less, it is possible to apply an appropriate voltage to the discharge wire 205 when obtaining a stable corona discharge, and it is possible to easily prevent the generation of ozone.
[0038] 2B, the flat grid 206 can be disposed between the discharge wire 205 and the mixture layer 401 disposed on the substrate 3. Here, from the viewpoint of making the charged potential on the surface of the mixture layer 401 uniform, the distance between the surface of the mixture layer 401 and the grid 206 is preferably in the range of 1 mm or more and 10 mm or less. However, when the mixture layer 401 does not contain a charge control agent, the above-mentioned charging process may result in the formation of convex bumps on the outer surface of the mixture layer 401. This is thought to be because unevenness in the surface potential occurs when the outer surface of the mixture layer 401 is charged, and the convex bumps are formed in parts with locally low surface potential. It is thought that the cause of the unevenness in the surface potential is shear unevenness in the preparation process of the addition-curing liquid silicone rubber mixture and variation in the surface composition of the thermally conductive filler. It is speculated that shear unevenness and variation in the surface composition of the thermally conductive filler cause parts with locally high charge in the thermally conductive filler, causing the surface potential of those parts to be low. However, when an addition-curing liquid silicone rubber mixture according to the present disclosure that contains a charge control agent is used, it is possible to prevent the occurrence of convex bumps on the outer surface. This is believed to be because the charge control agent makes the charge amount of the thermally conductive filler uniform, making it difficult for parts with locally high charge amounts to occur.
[0039] (4) Surface layer of fixing material The surface layer may be, for example, a fluororesin layer, more specifically, a layer made of any of the following resins: Examples of fluororesins include tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), polytetrafluoroethylene (PTFE), and tetrafluoroethylene-hexafluoropropylene copolymer (FEP). Furthermore, the surface layer may contain a filler for the purpose of improving thermal properties and abrasion resistance, within a range that does not impair moldability and toner releasability. The thickness of the surface layer (e.g., fluororesin layer) is preferably 10 μm or more and 100 μm or less. If the thickness of the surface layer is 10 μm or more, sufficient durability can be obtained. If the thickness is 100 μm or less, the excellent flexibility of the silicone rubber-containing elastic layer can function.
[0040] The method for forming the surface layer is not particularly limited, and for example, the following method 1) or 2) can be used. 1) Method of forming a surface layer by covering with fluororesin tube FIG. 4 is a schematic diagram for explaining the method 1) above. An adhesive is applied to the surface of an elastic layer 4 made of silicone rubber to form an adhesive layer 5. The adhesive will be described later. A fluororesin molded into a tube shape is coated on the outer surface of this adhesive layer 5 as a surface layer 6, and laminated. The inner surface of the fluororesin tube can be activated in advance by treating it with sodium, excimer laser, ammonia, or the like to improve adhesion.
[0041] The adhesive is preferably an addition-curing silicone rubber containing a self-adhesive component. Specifically, the silicone rubber may contain an organopolysiloxane having a plurality of unsaturated aliphatic groups, typically vinyl groups, in the molecular chain, a hydrogenorganopolysiloxane, and a platinum compound as a crosslinking catalyst. The silicone rubber cures by addition reaction. The adhesive made of such an addition-curing silicone rubber may be a known one.
[0042] When the base 3 is a core metal capable of retaining its shape, it is not necessary, but when using a thin-walled base such as a resin belt or a metal sleeve used in a belt-shaped fixing member, it is preferable to hold the base 3 by fitting it to the core in order to prevent deformation during processing. The method of covering the fluororesin tube is not particularly limited, but a method of covering it with an adhesive as a lubricant, a method of expanding the fluororesin tube from the outside, and the like can be used. After covering, the excess adhesive remaining between the elastic layer 4 made of silicone rubber and the fluororesin tube 6 can be removed by squeezing it out using a means not shown. The thickness of the adhesive layer 5 after being squeezed out is preferably 20 μm or less. If the thickness of the adhesive layer is 20 μm or less, it is easy to suppress the hardness increase of the fixing member, and when used as a fixing member, it has excellent conformability to the unevenness of the paper. Next, the adhesive layer is hardened by heating for a predetermined time with a heating means such as an electric furnace, and both ends are processed to a desired length as necessary, thereby obtaining the fixing member according to the present disclosure.
[0043] 2) Formation of the surface layer by fluororesin coating For the fluororesin coating process for forming the surface layer, methods such as electrostatic coating of fluororesin fine particles and spray coating of fluororesin paint can be used. When using the electrostatic coating method, first, electrostatic coating of fluororesin fine particles is performed on the inner surface of the mold, and the mold is heated to the melting point of the fluororesin or higher to form a thin film of fluororesin on the inner surface of the mold. After this, the inner surface is subjected to an adhesion treatment, and then the substrate is inserted. Between the substrate and the fluororesin, the addition-curing liquid silicone rubber mixture according to the present disclosure, which contains at least a thermally conductive filler, a negatively charged charge control agent, and, for example, an addition-curing liquid silicone rubber component, is injected. Then, the rubber mixture is cured and then demolded to obtain the fixing member according to the present disclosure.
[0044] (5) Manufacturing method of fixing member A method for producing a fixing member according to the present disclosure includes, for example, the following step of forming an elastic layer containing a silicone rubber. A step of preparing a liquid silicone mixture containing a liquid silicone polymer, a thermally conductive filler dispersed in the liquid silicone polymer, and a charge control agent having a negative charge with respect to the thermally conductive filler; forming a layer of said liquid silicone mixture on a surface of a substrate having an endless shape; a step of disposing a corona charger across the width of the substrate and facing the surface of the layer of the liquid silicone mixture; a step of charging the surface of the layer of the liquid silicone mixture using the corona charger; curing the layer of liquid silicone mixture to obtain the elastic layer. The method of manufacturing the fixing member according to the present disclosure may also include the following steps. A step of laminating an adhesive layer and a surface layer (e.g., a fluororesin surface layer) on an elastic layer containing silicone rubber. In addition, in the manufacturing method of the fixing member according to the present disclosure, the order of each process can be appropriately set, and these processes can be performed simultaneously (in parallel). When forming the surface layer, the above-mentioned method for forming the adhesive layer and the surface layer can be used.
[0045] (6) A fixing device in which the fixing member of the present disclosure is disposed The fixing device according to the present disclosure will be described. The fixing device according to the present disclosure is a fixing device used in an electrophotographic image forming apparatus, in which the fixing member according to the present disclosure is arranged as a fixing belt, a fixing roller, or a fixing film. The electrophotographic image forming apparatus includes an electrophotographic image forming apparatus having a photoconductor, a latent image forming means, a means for developing the formed latent image with toner, a means for transferring the developed toner image to a recording material, and a means for fixing the toner image on the recording material.
[0046] FIG. 5 is a schematic diagram showing the configuration of one embodiment of a fixing device according to the present disclosure. FIG. 5 is a schematic diagram showing an example of a fixing belt-pressure roller type thermal fixing device using a ceramic heater as a heating body. In FIG. 5, 501 is a fixing belt according to one embodiment of the present disclosure. The fixing belt 501 is loosely fitted around a belt guide 503. A pressure roller 509 is disposed below the fixing belt 501 so as to face the fixing belt 501. The pressure roller 509 has a core metal 509a and an elastic layer 509b containing silicone rubber provided on the outer circumferential surface of the core metal 509a. The pressure roller 509 is rotatably held by bearings between the front side chassis side plate and the rear side chassis side plate (not shown). The pressure roller 509 may be provided with a surface layer (not shown) containing a fluororesin such as PFA (tetrafluoroethylene / perfluoroalkyl ether copolymer) in order to improve the toner releasability of the surface. Pressure springs (not shown) are arranged between both ends of pressure rigid stay 507 and spring bearing members (not shown) on the chassis side of the fixing device, respectively, to apply a downward force to pressure rigid stay 507. As a result, a fixing nip N is formed between the lower surface of ceramic heater 505 arranged on the lower surface of belt guide 503 and the upper surface of pressure roller 509, with fixing belt 501 sandwiched therebetween. Pressure roller 509 is driven to rotate in the direction indicated by arrow 511 by a driving means (not shown). A rotational force acts on fixing belt 501 due to friction between the outer surfaces of pressure roller 509 and fixing belt 501 caused by the rotational drive of pressure roller 509. Then, fixing belt 501 rotates around belt guide 503 in the direction indicated by arrow 513 at a speed corresponding to the rotational speed of pressure roller 509, while its inner surface slides in close contact with the lower surface of ceramic heater 505 at fixing nip portion N. Based on a print start signal, the pressure roller 509 starts rotating, and the ceramic heater 505 starts heating. After that, the recording medium S carrying the unfixed toner image t as the material to be heated is introduced between the fixing belt 501 and the pressure roller 509 in the fixing nip N, with the toner image carrying surface side facing the fixing belt 501. Then, the recording medium S is brought into close contact with the lower surface of the ceramic heater 505 via the fixing belt 501 in the fixing nip N, and moves through the fixing nip N together with the fixing belt 501. In the process, the heat of the fixing belt 501 is applied to the recording medium S, and the toner image t is fixed on the surface of the recording medium S. The recording medium S that has passed through the fixing nip N is separated from the outer surface of the fixing belt 501 and is transported. Ceramic heater 505 as a heating element has heater substrate 505a made of aluminum nitride, heat generation layer 505b provided on the surface of heater substrate 505a along the longitudinal direction thereof, and protective layer 505c formed of a material having excellent heat resistance such as glass or fluororesin provided thereon. Heat generation layer 505b is made of an electric resistance material such as Ag / Pd (silver / palladium) with a thickness of 10 μm and a width of 1 to 5 mm by screen printing or the like. When electricity is applied to both ends of the heat generating layer 505b of the ceramic heater 505, the heat generating layer 505b generates heat, and the temperature of the ceramic heater 505 rises. The ceramic heater 505 is fixed by fitting the protective layer 505c upward into a groove formed along the longitudinal direction of the belt guide 503 at approximately the center of the lower surface of the belt guide 503. In the fixing nip N that contacts the fixing belt 501, the surface of the sliding member 505d of the ceramic heater 505 and the inner peripheral surface of the fixing belt 501 contact and slide against each other. A temperature detection element 515 for controlling the temperature of the ceramic heater 505 is provided on the protective layer 505c. As described above, in the thermal fixing device using the fixing belt 501 according to the present disclosure as a heating belt, the heat supplied to the fixing belt by the heating means (heater) arranged in contact with the inner circumferential surface of the fixing belt 501 easily flows in the thickness direction of the elastic layer. Therefore, the energy input to the fixing belt can be efficiently utilized for thermal fixing of unfixed toner. Although a fixing device having a fixing belt and a pressure roller has been given as an example here, the fixing device according to the present disclosure need only have the fixing member according to the present disclosure as a fixing belt, fixing roller or fixing film, and is not limited to the one shown in FIG. 5.
[0047] According to one aspect of the present disclosure, it is possible to obtain an electrophotographic fixing member having excellent durability, in which the elastic layer containing a thermally conductive filler does not break or plastically deform even after long-term use. According to another aspect of the present disclosure, it is possible to obtain a fixing device and an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. EXAMPLES
[0048] The present disclosure will now be described in more detail with reference to examples. First, a method for determining whether a charge control agent is negatively or positively charged with respect to a thermally conductive filler will be described. A solution in which a charge control agent is dissolved is spin-coated to form a film made of the charge control agent. A thermally conductive filler is placed on the film, and the charge control agent and the thermally conductive filler are rubbed together by moving the film or the like. The surface potential of the film at that time is measured, and it is possible to determine whether the film is negatively or positively charged from the result of whether it is negatively or positively charged.
[0049] Next, the method for measuring the thermal decomposition onset temperature of the charge control agent will be described. Using a thermogravimetric analyzer (TGA / SDTA851e, manufactured by METTLER TOLEDO), the temperature was raised from 40°C to 400°C at a rate of 3°C / min. The onset temperature of the sample weight curve during the temperature rise (the intersection point between the tangent at the inflection point of the curve and the extension of the baseline) was taken as the thermal decomposition onset temperature.
[0050] Next, a method for evaluating the dispersion state of the charge control agent will be described. First, the cross section of the elastic layer is polished using an ion beam. For example, a cross-section polisher can be used for polishing the cross section with an ion beam. In polishing the cross section with an ion beam, it is possible to prevent the filler from falling off the sample and the abrasive from being mixed in, and it is also possible to form a cross section with few polishing marks. The cross section of the elastic layer thus formed was evaluated by measuring the distribution of ions believed to be derived from the charge control agent using time-of-flight secondary ion mass spectrometry (TOF-SIMS) after sputter cleaning of the sample surface.
[0051] Example 1 (1) Preparation of addition-curing liquid silicone rubber mixture; First, as component a, a silicone polymer (viscosity 5000 mm) having vinyl groups, which are unsaturated aliphatic groups, only at both ends of the molecular chain and having methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups was used. 2 100 parts by mass of 1,2-dichloro-2,3-difluorophenyl ether (Vi) was prepared. Next, 271.4 parts by mass of magnesium oxide powder (product name: SL-WR, manufactured by Konoshima Chemical Co., Ltd.) was weighed out and added to Vi. Next, 3 parts by mass of sodium=bis{1-[(5-chloro-2-hydroxyphenyl)azo]-phenylcarbamoyl)-2-naphtholato}iron(III) (product name: S-215S, manufactured by Orient Chemical Industry Co., Ltd., thermal decomposition starting temperature 312°C), which is a negatively charged charge control agent for the magnesium oxide powder, was weighed out and added to Vi. Next, 0.1 part by mass of 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane (product name: SIT7900.0, manufactured by Gelest Co., Ltd.), which is a cure retarder as component (d), was added to the mixture of Vi and magnesium oxide powder. Next, 0.03 parts by mass of a hydrosilylation catalyst (platinum catalyst, product name: SIP6829.2, manufactured by Gelest Co., Ltd.) as component c was added to the mixture of Vi, magnesium oxide powder, and cure retarder. Furthermore, as component b, a silicone polymer (viscosity 30 mm) having a linear siloxane skeleton and having active hydrogen groups bonded to silicon only on the side chains is used. 2 1.2 parts by mass of Vi / s, hereafter referred to as "SiH") was weighed out. This was added to a mixture of Vi, magnesium oxide powder, a negative charge control agent, a cure retarder, and a platinum catalyst, and mixed thoroughly to obtain an addition-curing liquid silicone rubber mixture containing 43 volume% magnesium oxide powder.
[0052] (2) Formation of an elastic layer; Next, a fixing belt was produced as follows using the obtained magnesium oxide powder and an addition-curing liquid silicone rubber mixture containing a negatively charged charge control agent. An endless sleeve made of nickel electroformed with an inner diameter of 30 mm, a width of 400 mm, and a thickness of 40 μm was prepared as a substrate. During the series of manufacturing processes, the endless sleeve (endless sleeve) was handled with a core inserted therein. First, a primer (product name: DY39-051 A / B, manufactured by Dow Corning Toray Co., Ltd.) was applied almost uniformly to the outer peripheral surface of the substrate, and after the solvent was dried, the substrate was baked in an electric furnace at a temperature of 160° C. for 30 minutes. The silicone rubber mixture was applied to this primer-treated substrate by ring coating to a thickness of 300 μm to form a mixture layer. Next, a corona charger 2 was placed so that its longitudinal direction was approximately parallel to the axial direction (longitudinal direction) of the substrate 3 on which the mixture layer was formed (see FIG. 2). Then, while the substrate on which the mixture layer was formed was rotated at 141 rpm, the surface of the mixture layer was charged using the corona charger. The charging conditions were as follows: Current supplied to the corona charger wire: AC 0.7Hz ±150μA (square wave) Grid electrode potential AC 0.7Hz ±900V (square wave) -Charging time 160 seconds Distance between grid electrode and silicone rubber mixture applied to substrate before curing 1: 3 mm
[0053] Next, the substrate having the charged surface mixture layer was placed in an electric furnace and heated at 160°C for 1 minute to cure the mixture layer first, and then heated at 200°C for 30 minutes to cure the mixture layer secondarily. Thus, an elastic layer was formed. In the obtained elastic layer, the charge control agent was dispersed in the form of particles with a diameter of 1 μm. (3) Evaluation of elastic layer properties
[0054] (3-1) Hardness and breaking energy measurement of elastic layer The hardness of the elastic layer was measured in peak hold mode using a micro rubber hardness tester (MD-1 Type C, manufactured by Kobunshi Keiki Co., Ltd.). The measurement was performed by contacting the indenter of the micro rubber hardness tester with the surface of the elastic layer opposite the substrate side at a total of 40 points, including 8 points in the circumferential direction of the elastic layer and 5 points in the direction perpendicular to the circumferential direction, and the average value of the measured values was used as the value of this evaluation. The hardness measurement was performed in an environment with a temperature of 23°C and a relative humidity of 40%. The breaking energy of the elastic layer was measured by cutting out a measurement sample from the elastic layer using a punching die specified in Japanese Industrial Standards (JIS) K 6251-8, and measuring the rubber thickness near the center, which was the measurement point. Next, the measurement sample was tested at room temperature (25°C) using a tensile tester (product name: Strograph EII-L1, manufactured by Toyo Seiki Seisakusho Co., Ltd.) at a tensile speed of 200 mm / min. The breaking energy was measured by creating a graph from the measurement results with the sample distortion on the horizontal axis and the tensile stress on the vertical axis, and the area obtained by integrating the measurement data in the range from 0% distortion to the distortion at which the rubber broke was used. As a result, the hardness of the elastic layer was 74°, and the breaking energy was 23 kJ / m 2 It was.
[0055] (3-2) Heat capacity per unit volume of the elastic layer The heat capacity per unit volume, CV, was calculated from the following formula: CV = CP × ρ In the formula, Cp is the specific heat at constant pressure (J / (kg K)), ρ is the density (kg / m 3 ) The values of the specific heat at constant pressure and the density in the above formula were determined by the following method. Constant pressure specific heat CP The constant pressure specific heat of the elastic layer was measured using a differential scanning calorimeter (product name: DSC823e, manufactured by Mettler Toledo K.K.). Specifically, aluminum pans were used as the sample pan and the reference pan. First, as a blank measurement, both pans were empty and kept at a constant temperature of 15°C for 10 minutes, then the temperature was raised to 215°C at a rate of 10°C / min, and the temperature was kept constant at 215°C for another 10 minutes. Next, 10 mg of synthetic sapphire with a known constant pressure specific heat was used as the reference material, and measurements were performed using the same program. Next, a measurement sample of 10 mg, the same amount as the reference sapphire, was cut out from the elastic layer, set in the sample pan, and measurements were performed using the same program. These measurement results were analyzed using the specific heat analysis software attached to the differential scanning calorimeter, and the constant pressure specific heat CP at 25°C was calculated from the average value of five measurement results. As a result, the constant pressure specific heat of the silicone rubber-containing elastic layer was 1.12 J / (g·K). ·Density ρ The density of the elastic layer was measured using a dry automatic densitometer (product name: Accupyc 1330-01, manufactured by Shimadzu Corporation). Specifically, 10 cm 3 A sample was cut out from the elastic layer so as to fill approximately 80% of the cell volume, and the mass of the sample was measured and then placed in the sample cell. This sample cell was set in the measuring section of the device, and after gas replacement using helium as the measuring gas, the volume was measured 10 times. The density of the sample was calculated from the mass of the sample and the measured volume for each measurement, and the average value was calculated. As a result, the density of the silicone rubber-containing elastic layer was found to be 2.05 g / cm 3 The heat capacity per unit volume CV was calculated from the constant pressure specific heat CP and density ρ of the silicone rubber-containing elastic layer thus obtained, and was found to be 2.30 MJ / m 3 It was K.
[0056] (3-3) Thermal conductivity in the thickness direction of the elastic layer The thermal conductivity λ of the elastic layer in the thickness direction was calculated from the following formula. λ=α×Cp×ρ In the formula, λ is the thermal conductivity of the elastic layer in the thickness direction (W / (m K)), α is the thermal diffusivity in the thickness direction (m2 / s), Cp is the specific heat at constant pressure (J / (kg K)), and ρ is the density (kg / m 3 Here, the constant pressure specific heat Cp and density ρ of the elastic layer were converted into units of the values obtained by the above-mentioned method. The thermal diffusivity in the thickness direction was obtained by the following method. ·Thermal diffusivity α The thermal diffusivity in the thickness direction of the elastic layer was measured at room temperature (25°C) using a periodic heating method thermal property measurement device (product name: FTC-1, manufactured by ULVAC-RIKO, Inc.). The elastic layer was cut with a cutter into sample pieces with an area of 8 x 12 mm to prepare a total of five samples, and the thickness of each sample was measured. Next, each sample was measured five times in total, and the average value (m 2 The unit-converted specific heat at constant pressure Cp (J / (kg K)) and density ρ (kg / m 3 ), and the measured thermal diffusivity α(m 2 The thermal conductivity λ of the silicone rubber-containing elastic layer was calculated from the thermal conductivity (Tc) of the elastic layer and found to be 1.3 W / (m K). (4) Preparation of the fixing belt A substrate having an elastic layer was prepared in the same manner as in (1) to (3) above. Next, while rotating the substrate so that the surface of the elastic layer was rotating at a speed of 20 mm / sec in the circumferential direction, the surface of the elastic layer was irradiated with ultraviolet light using an ultraviolet lamp installed at a distance of 10 mm from the surface of the elastic layer. A low-pressure mercury ultraviolet lamp (product name: GLQ500US / 11, manufactured by Toshiba Lighting & Technology Corporation (formerly Harrison Toshiba Lighting Corporation)) was used as the ultraviolet lamp, and irradiation was performed in the air at room temperature (temperature of 25°C) for 6 minutes.
[0057] Next, an addition-curing silicone rubber adhesive (product name: SE1819CV A / B, manufactured by Toray Dow Corning Co., Ltd.) was applied to the ultraviolet-irradiated surface of the elastic layer to a thickness of 20 μm. Next, a fluororesin tube (product name: KURANFL ON-LT, manufactured by Kurabo Industries Co., Ltd.) with an inner diameter of 29 mm and a thickness of 30 μm was laminated on the adhesive to produce an endless belt. Next, this endless belt was heated at a temperature of 200° C. for 1 hour in an electric furnace to cure the adhesive and fix the surface layer made of the fluororesin tube on the elastic layer. Next, both ends of the endless belt with the fluororesin tube fixed on the elastic layer were cut to obtain a fixing belt with a width of 341 mm.
[0058] (5) Evaluation of fixing belt (5-1) Evaluation of pressure resistance and durability of elastic layer The fixing belt produced in (4) above was cut open in a direction perpendicular to its circumferential direction to form a single sheet, and four samples measuring 50 mm long x 50 mm wide were cut out from the sheet. The sample was evaluated for pressure resistance durability using a jig shown in FIG. 6. Specifically, the sample 601 was placed on a stainless steel plate 605 placed on a heater 603 so that the surface layer side of the sample 601 was in contact with the stainless steel plate 605. The temperature of the surface 601-1 of the elastic layer of the sample 601 was adjusted to 240° C. using a thermistor 607 placed on the surface 601-1. The pressing roller 609 (width 10 mm, diameter 15 mm) was pressed on the surface 601-1 with a load of 10 N, while rotating in the direction of an arrow 611 and reciprocating on the surface 601-1 in the direction of an arrow 613. In this way, the time until the elastic layer of the sample 601 was broken by visual observation (hereinafter, also referred to as the “breakage time”) was measured. The average value of the breakage times of the four samples was calculated to be the evaluation result of the pressure resistance durability of the elastic layer of the fixing belt according to this embodiment.
[0059] (5-2) Actual machine evaluation (i) The fixing belt prepared in the same manner as in (4) above was attached to the fixing device of a full-color electrophotographic image forming apparatus (product name: imageRUNNERADVANCE C5051; manufactured by Canon Inc.). Using this multifunction machine, cyan solid images were continuously formed on 300,000 sheets of A4-sized plain paper. The 10th image (hereinafter, "initial image") and the 300,000th image (hereinafter, "durable image") were visually observed, and the presence or absence of gloss unevenness was evaluated according to the following criteria. Rank A: No uneven gloss caused by poor fixing is observed. Rank B: Slight unevenness in gloss due to poor fixing is observed. Rank C: Gloss unevenness due to poor fixing is clearly observed. (ii) The fixing belt used in the above (i) for forming 300,000 images was removed from the fixing device. The hardness was measured by contacting the surface of the surface layer of the removed fixing belt with the indenter of a micro rubber hardness tester (MD-1 Type C, manufactured by Kobunshi Keiki Co., Ltd.). The hardness was measured in an environment of a temperature of 23°C and a relative humidity of 40%. The difference in hardness between the surface of the surface layer of the fixing belt before being used for forming 300,000 images, which was measured in advance by the same method as above, was calculated.
[0060] [Examples 2 to 3] A liquid addition curing type silicone rubber mixture was prepared in the same manner as in Example 1, except that the amount of the charge control agent was 1 part by mass or 5 parts by mass. An elastic layer was formed on a substrate in the same manner as in Example 1, except that this addition curing type liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 1, except that the addition curing type liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1. Example 4 An addition curing type liquid silicone rubber mixture was prepared in the same manner as in Example 1, except that aluminum 3,5-di-tert-butyl salicylate (product name: E-101, manufactured by Orient Chemical Industry Co., Ltd., thermal decomposition starting temperature 203°C) was used as a charge control agent. An elastic layer was formed on a substrate in the same manner as in Example 1, except that this addition curing type liquid silicone rubber mixture was used. The properties of the obtained elastic layer were evaluated in the same manner as in Example 1. A fixing belt was also produced and evaluated in the same manner as in Example 1, except that the addition curing type liquid silicone rubber mixture prepared above was used. The results of the property evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0061] Example 5 Component a is a silicone polymer (viscosity 20,000 mm) having vinyl groups, which are unsaturated aliphatic groups, at both ends of the molecular chain and in the side chains, and having methyl groups as unsubstituted hydrocarbon groups that do not contain other unsaturated aliphatic groups. 2 An addition-curing liquid silicone rubber mixture was obtained in the same manner as in Example 1, except that 162.2 parts by mass of metal silicon powder (product name: #600WB, manufactured by Kinsei Matec Co., Ltd.) was used as the thermally conductive filler. The volumetric proportion of the metal silicon powder in the resulting addition-curing liquid silicone rubber mixture was 40% by volume. Except for using this addition-curing liquid silicone rubber mixture, an elastic layer was formed on a substrate in the same manner as in Example 1. The obtained elastic layer was subjected to property evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 1, except for using the addition-curing liquid silicone rubber mixture prepared above. The results of the property evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0062] Example 6 An addition curing liquid silicone rubber mixture was obtained in the same manner as in Example 5, except that bis[1-(5-chloro-2-hydroxyphenylazo)-2-naphtholato]chromium(III) iron (trade name: S-34, manufactured by Orient Chemical Industry Co., Ltd., thermal decomposition starting temperature 325°C) was used as a charge control agent. An elastic layer was formed on a substrate in the same manner as in Example 1, except that this addition curing liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 1, except that the addition curing liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0063] Example 7 An addition curing liquid silicone rubber mixture containing 35% by volume of zinc oxide powder was obtained in the same manner as in Example 1, except that 317 parts by mass of zinc oxide powder was used as a thermally conductive filler. An elastic layer was formed on a substrate in the same manner as in Example 1, except that this addition curing liquid silicone rubber mixture was used and the surface of the addition curing liquid silicone rubber mixture layer was not subjected to an electrostatic charging treatment. The obtained elastic layer was subjected to a characteristic evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 1, except that the addition curing liquid silicone rubber mixture prepared above was used and the surface of the addition curing liquid silicone rubber mixture layer was not subjected to an electrostatic charging treatment. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0064] Example 8 An addition curing type liquid silicone rubber mixture containing 46% by volume of alumina powder was obtained in the same manner as in Example 5, except that 350 parts by mass of alumina powder was used as the thermally conductive filler. An elastic layer was formed on a substrate in the same manner as in Example 7, except that this addition curing type liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 7, except that the addition curing type liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0065] Example 9 Except for not carrying out the electrostatic treatment on the surface of the addition curing type liquid silicone rubber mixture layer, an elastic layer was formed on a substrate in the same manner as in Example 1. The properties of the obtained elastic layer were evaluated in the same manner as in Example 1. A fixing belt was produced and evaluated in the same manner as in Example 1, except that the surface of the addition curing type liquid silicone rubber mixture layer was not subjected to an electrostatic charging treatment. The results of the property evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0066] Example 10 Except for not carrying out the electrostatic treatment on the surface of the addition curing type liquid silicone rubber mixture layer, an elastic layer was formed on a substrate in the same manner as in Example 5. The properties of the obtained elastic layer were evaluated in the same manner as in Example 1. A fixing belt was also produced and evaluated in the same manner as in Example 5, except that the surface of the addition-curing liquid silicone rubber mixture layer was not subjected to the charging treatment. Table 1 shows the results of the evaluation of the properties of the elastic layer and the evaluation results as a fixing belt.
[0067] Comparative Example 1 An addition-curing liquid silicone rubber mixture containing 43 volume % magnesium oxide powder was obtained in the same manner as in Example 1, except that no charge control agent was used. An elastic layer was formed on a substrate in the same manner as in Example 1, except that this addition-curing liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 1, except that the addition-curing liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0068] Comparative Example 2 An addition curing type liquid silicone rubber mixture containing 40 volume % of metal silicon powder was obtained in the same manner as in Example 5, except that no charge control agent was used. An elastic layer was formed on a substrate in the same manner as in Example 5, except that this addition curing type liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 1. In addition, a fixing belt was produced and evaluated in the same manner as in Example 5, except that the addition curing type liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0069] Comparative Example 3 An addition curing type liquid silicone rubber mixture containing 35 volume % zinc oxide powder was obtained in the same manner as in Example 7, except that no charge control agent was used. An elastic layer was formed on a substrate in the same manner as in Example 7, except that this addition curing type liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 7. In addition, a fixing belt was produced and evaluated in the same manner as in Example 7, except that the addition curing type liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0070] Comparative Example 4 An addition curing type liquid silicone rubber mixture containing 46 volume % of alumina powder was obtained in the same manner as in Example 8, except that no charge control agent was used. An elastic layer was formed on a substrate in the same manner as in Example 8, except that this addition curing type liquid silicone rubber mixture was used. The obtained elastic layer was subjected to characteristic evaluation in the same manner as in Example 8. In addition, a fixing belt was produced and evaluated in the same manner as in Example 8, except that the addition curing type liquid silicone rubber mixture prepared above was used. The results of the characteristic evaluation of the elastic layer and the evaluation results as a fixing belt are shown in Table 1.
[0071] [Table 1]
[0072] [Evaluation results] The evaluation results of the examples and comparative examples shown in Table 1 above will be described. The elastic layers according to Examples 1 to 10, which contain a negatively charged charge control agent, have a larger breaking energy and improved pressure resistance durability compared to the elastic layers according to the comparative examples. Furthermore, even after forming images on 300,000 sheets, the fixing belts according to Examples 1 to 10 did not show any breakage of the elastic layer in the non-paper passing portion of the fixing belt, which is prone to breakage due to contact with the edge of the paper. [Explanation of symbols]
[0073] 3 Base 4 Elastic layer 4a Silicone rubber 4b Thermally conductive filler 4c Negative charge control agent 6 Surface layer
Claims
1. 1. An electrophotographic fixing member having, in this order, a substrate, an elastic layer on the substrate, and a surface layer, the elastic layer includes a silicone rubber and a thermally conductive filler dispersed in the silicone rubber; The thermally conductive filler is a metal oxide particle or a metal particle at least a part of whose surface is composed of a metal oxide, The electrophotographic fixing member is characterized in that the elastic layer further contains a charge control agent which is negatively chargeable with respect to the thermally conductive filler.
2. 2. The fixing member for electrophotography according to claim 1, wherein the thermally conductive filler is at least one selected from the group consisting of magnesium oxide, metallic silicon, alumina and zinc oxide.
3. 3. The fixing member for electrophotography according to claim 1, wherein the charge control agent has a thermal decomposition starting temperature of 300[deg.] C. or higher.
4. 4. The fixing member for electrophotography according to claim 1, wherein the charge control agent is an azo metal complex.
5. The electrophotographic fixing member according to claim 4, wherein the azo metal complex is a compound represented by the following structural formula (i) or (ii): 【Chemistry 1】
6. 6. The fixing member for electrophotography according to claim 1, wherein the amount of the charge control agent is 1 part by mass or more and 5 parts by mass or less based on 100 parts by mass of the silicone rubber.
7. 7. The fixing member for electrophotography according to claim 1, wherein the charge control agent is dispersed in the silicone rubber in the form of particles having a diameter of 1 [mu]m or less.
8. A fixing device comprising a heating member and a pressure member disposed opposite to the heating member, wherein at least one of the heating member and the pressure member is an electrophotographic fixing member having a substrate, an elastic layer on the substrate, and a surface layer in this order, the elastic layer includes a silicone rubber and a thermally conductive filler dispersed in the silicone rubber; The thermally conductive filler is a metal oxide particle or a metal particle at least a part of whose surface is composed of a metal oxide, The elastic layer further comprises a charge control agent that is negatively charged with respect to the thermally conductive filler. A fixing device comprising:
9. An electrophotographic image forming apparatus having a fixing device, The fixing device includes a heating member and a pressure member disposed opposite the heating member, At least one of the heating member and the pressure member is an electrophotographic fixing member having a substrate, an elastic layer on the substrate, and a surface layer in this order, the elastic layer includes a silicone rubber and a thermally conductive filler dispersed in the silicone rubber; The thermally conductive filler is a metal oxide particle or a metal particle at least a part of whose surface is composed of a metal oxide, The elastic layer further comprises a charge control agent having a negative charging property with respect to the thermally conductive filler.
Citation Information
Patent Citations
externally heated deformable fuser roller
DE10148939A1
Fixing roll, silicone rubber composition for fixing roll and production thereof
JP1991221982A
Outside heating type deformable fusing roller
JP2002116648A
Fixing member and fixing device
JP2005300591A
Silicone rubber composition for high-heat-conductivity heat fixing roll or fixing belt, and heat fixing roll or fixing belt
JP2007171946A